The invention of feminist criminology: foundational perspectives - Cullen, Francis T. (Gender and crime, 2024)
Starting in 1975, four “sisters in criminology” wrote important books that challenged past attempts to attribute female offending to biological and psychological defects that caused women to depart from the traditional goals of wife and motherhood. These works “invented” feminist criminology by illuminating the significance of focusing on women and crime and by providing thoroughly sociological frameworks to guide these efforts. Their publication, independently and collectively, made it impossible heretofore to ignore women as a core part of the criminological enterprise. In Sisters in Crime: The Rise of a New Female Criminal, Freda Adler (1975) made the boldest claim that gender-role convergence was rapidly increasing women’s participation in a range of crimes. In Women and Crime, Rita Simon (1975) argued that access to new occupational opportunities would foster, among other property crimes, white-collar offenses. In Women, Crime and Criminology: A Feminist Critique, Carole Simon (1977) studied similar issues in the United Kingdom and encouraged a more leftist perspective that rooted the status of women in socio-political realities. And in Women, Crime, and Society: A Critique of Criminological Theory, Eileen Leonard (1982) argued that, although increases in crime had occurred, the main task was to explain why women remained far more likely than men to be noncriminals. These works should be revisited today both for their historical value and for the insights they convey that are of enduring value.